Reaktivasi Klaim BPJS sebagai Cerminan Kualitas Rekam Medis Elektronik: Studi di Rumah Sakit Tahun 2025 - I Gusti Agung Ngurah Putra Pradnyantara; Harinto Nur Seha; Nurul Dwi Andriani (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2026)
BPJS claim reactivation is a process of resubmitting rejected claims due to discrepancies in medical record data and administrative requirements. In claim-based healthcare financing systems, the quality of Electronic Medical Records (EMR) plays a crucial role in determining the success of claim verification and reimbursement. A high reactivation rate may indicate underlying issues in the quality of clinical and administrative data recorded in EMR systems. This study aims to analyze BPJS claim reactivation as a reflection of EMR quality in a hospital in 2025. This study employed a quantitative approach with a descriptive-analytic design. The sample was determined using total sampling, consisting of 3,843 reactivation cases out of 11,299 submitted claims. Data were obtained from BPJS claim reports and the EMR system and analyzed descriptively. The results showed that the reactivation rate reached 34% of total claims. The distribution of reactivation was fluctuating, with the highest number in February due to backlog accumulation and in October indicating actual issues in claim management. The high reactivation rate suggests that EMR quality is not yet optimal, particularly in terms of completeness, accuracy, and timeliness of data entry. In conclusion, BPJS claim reactivation can be used as an indirect indicator to assess EMR quality. Therefore, efforts are needed to improve EMR quality through better documentation standards, enhanced staff competency, and optimization of health information systems. Keywords: claim reactivation, BPJS, electronic medical records, data quality, healthcare quality